USING NOTE TAKING STRATEGY TO ENHANCE STUDENTS’ LISTENING COMPREHENSION ABILITY - Adi Novrian Jamil; Deddy Suezdy (Lingua, 2018)
This article points out the results of the research investigating the effect of note takingstrategy on the third semester students’ listening comprehension of English Education StudyProgram, Faculty of Teaching and Educational Sciences, Universitas Islam As-Syafi’iyahJakarta. The research samples were taken using purposive sampling, with the total numberof samples is 30 students.The research methodology was pre-experiment method, with onegrouppretest posttest design. Data collection procedure was completed by the students byobtaining scoresin the listening section of PET test,30 items.The findings indicated that therewas significant difference of score between the students who received note taking strategyand students who did not receive note taking strategy. It can be seen from the data analysisusing ANOVA that showed significance value of 0.000 was smaller than (<) Alpha 0.05 andFobserved (15.873) is higher than the critical value of Ftable(2.35). It means that note takingstrategy has significant effect on students’ listening comprehension ability.The Implicationof result research can benefit both lecturer and students in listening comprehension strategy.